Identificação molecular de isolados de Ralstonia sp. da cultura do tomateiro no sudoeste do Paraná - Zanon, Vanessa Casiraghi (2019)
One of the main diseases of tomato is bacterial wilt, caused by the species Ralstonia solanacearum and R. pseudosolanacearum . They are complex species, formed by variants with high diversity in terms of adaptation to different climatic conditions, host circle and aggressiveness, among others, characteristics that interfere in the recommendation of disease control. The control of the disease is difficult, and the main measure is to avoid the entrance of the bacterium in the area of planting. The objective of th is work was to molecularly identify 46 isolates of the agent responsible for the green wilt of tomato plants grown in the Southwest region of Paraná. The isolates of Ralstonia sp. were obtained from plants with wilt symptoms cultivated in a protected field system and open field. For isolation the Kelman medium was used from millet filament exudation of the stem portions of the infected plant when placed in contact with autoclaved water. DNA extraction from 46 isolates was performed according to the methodol ogy of Mahuku (2004) and then used in the molecular analyzes. Initially, to confirm whether the isolates belonged to the R. solanacearum complex, specific primers 759/760 were used. Then, to identify which phylotype the bacterial isolates belonged to, a se t of five Nmult primers were used, which generate fragments of different sizes for each phylotype. Finally, the BOX PCR technique was used to characterize 21 isolates that confirmed the etioloagy using primers 759/760, which allowed the construction of a b inary matrix with the fragments generated in the amplification. A dendrogram was then constructed using the UPGMA method using the Jaccard coefficient of similarity. DNA amplification of 28 isolates with fragments of 280 bp indicated the pathogen as belong ing to the R. solanacearum species and the DNA amplification of 26 isolates positioned all the isolates in the philotype II, from the Americas. The comparison between the standards of BOX PCR amplified genomic DNA bands indicated molecular diversity in the population with the formation of five groups at the level of 0.31 of similarity, which may or may not be associated with differentiated patterns of aggressiveness or virulence. The results of this work contributed to a better understanding of the geograph ical distribution of the pathogen in the region and to help in genetic improvement work to obtain tomato cultivars resistant to R. solanacearum.